Accounting fraud : maneuvering and manipulation, past and present - Giroux, Gary A. (New York, New York (222 East 46th Street, New York, NY 10017) : Business Expert Press, 2014)
Scandals relating to manipulation and fraud have dominated much of the history of business and the accounting profession in America since its founding. Crooks, corruption, scandals, and panics have been regular features of the business landscape ever since, with regulations and the expansion of financial disclosure, auditing, and regulatory agencies following major debacles. Prior to the creation of the Securities and Exchange Commission (SEC) in the 1930s and the development of generally accepted accounting principles (GAAP), few accounting rules existed and it is difficult to identify "accounting" scandals. Consequently, the primary focus is the post-World War II period, when accounting manipulation and fraud can be identified based on specific accounting violations. The importance of this topic is demonstrated by the major accounting and finance scandals of the 21st century, some of the most destructive in our history.
Introduction -- 1. Accounting scandals, a historical perspective -- 2. Business and scandals before the Securities and Exchange Commission -- 3. Great Depression and reforms -- 4. War and post-World War II business and corruption -- 5. Tech bubble, bust, and bankruptcies -- 6. Subprime meltdown and beyond -- 7. The future of fraud and scandals -- Timeline -- Notes -- Bibliography -- Index.
Part of: 2014 digital library.
Includes bibliographical references (pages 161-172) and index.
Title from PDF title page (viewed on January 3, 2014).
Electronic reproduction. Ann Arbor, MI : ProQuest, 2015. Available via World Wide Web. Access may be limited to ProQuest affiliated libraries.
Keywords: Accounting fraud -- United States; accounting fraud; accounting standards; auditors; big 4 accounting firms; corporate fraud; earnings manipulation; earnings quality; Enron; Sarbanes-Oxley act; securities and exchange commission; subprime meltdown; transparency; WorldCom; Electronic books